The Personal and Political Response in W.B Yeat's "Easter 1916" - Shihan Muslih, Waleed (International Journal of Psychosocial Rehabilitation, 2020)
One of the troubling issues in "Easter, 1916" by William Butler Yeats (1865-1939) is the use of some ambiguous expressions by the poet in presenting the subject matter of the poem. This ambiguity reflects a duality in the poet's attitude towards the events in 1916. He is not completely consistent with the revolutionaries. In some parts of the poem, the poet is with the Irish rebels, whereas in other parts of the poem, he is against them. However, the present paper therefore aims to research the explanation behind the dual attitude of the poet in the poem. In terms of methodology, the present paper gives a summary of the poem; then it moves to some different aspects of poetic reaction and situations such as rational versus emotional, individual prejudice, and conformity. The study found out that the ambivalence in "Easter 1916" is caused by the intervention between the poet's personal and political visions.